(untitled) (Clinics, 2009)
INTRODUCTION: The present study examines cardiovascular risk factor profiles and 24-month mortality in patients with symptomatic peripheral arterial disease. DESIGN STUDY: Prospective observational study including 75 consecutive patients with PAD (67 ± 9.7 years of age; 52 men and 23 women) hospitalized for planned peripheral vascular reconstruction. Doppler echocardiograms were performed before surgery in 54 cases. Univariate analyses were performed using Student's t-test or Fisher's exact test. Survival analysis at 24-month follow-up was performed using the Cox regression model and Kaplan-Meier method including age and chronic use of aspirin as covariates. Survival curves were compared using the log-rank test. RESULTS: Hypertension and smoking were the most frequent risk factors (52 cases and 51 cases, respectively), followed by diabetes (32 cases). Undertreated dyslipidemia was found in 26 cases. Fasting glycine levels (131 ± 69.1 mg/dl) were elevated in 29 cases. Myocardial hypertrophy was found in 18 out of 54 patients. Thirty-four patients had been treated with aspirin. Overall mortality over 24 months was 24% and was associated with age (HR: 0.064; CI95: 0.014-0.115; p=0.013) and lack of use of aspirin, as no deaths occurred among those using this drug (p